el autismo infantil: una mirada crítica y simbólica desde la fotografía artística - Leon Balcazar, Shirley Dayana (Machala, 2025)
This research aims to make visible the problems that children with autism spectrum disorder (ASD) face in developing in a family, educational, cultural and social environment. Through a practical artistic workshop with children with ASD, since it is important to address this problem to highlight the importance of inclusion and support for children with ASD in their environment. Through art and in particular photography as a tool, which promotes the inclusion of these children in the fields noted above, raising awareness and encouraging positive changes that facilitate their integration and well-being. Art as a means to reflect the integration difficulties of autistic children in the Language Therapy Center (CTL) of the city of Huaquillas. Autistic children face numerous problems in developing in family, educational, cultural and social environments. In the family context, they may have difficulty communicating and forming emotional bonds with their loved ones. In addition, in the educational field, they often face barriers in learning and socialization, which can lead to exclusion and isolation of children with ASD. This segment of the population is often misunderstood, which makes it difficult for them to integrate into community activities. The lack of understanding and acceptance by a part of society can lead to discrimination and rejection. This study is interested in the problems of children with ASD, art has the power to communicate and make these experiences visible in a deep and accessible way. Likewise, it is considered worthy of being studied from the arts because the works can reflect the complex realities that these children face, generating empathy and awareness in the community. The relationship of art with this object of study lies in its ability to question and challenge social perceptions, promoting positive changes in the inclusion and support of autistic children. Consequently, art not only documents their challenges, but also offers a platform to express their voices and experiences; to transform attitudes and foster greater understanding and acceptance in society.
Este trabajo de investigación pretende visibilizar los problemas que enfrentan los niños con Trastorno del Espectro Autista (TEA) desenvolverse en un entorno familiar, educativo, cultural y social. A través de un taller práctico artístico con niños con TEA, ya que es importante abordar esta problemática para destacar la importancia de la inclusión y el apoyo a los niños con TEA en su entorno. Mediante el arte y en particular la fotografía como una herramienta, que promueva la inclusión de estos niños en los campos antes anotado, creando conciencia y fomentando cambios positivos que faciliten su integración y bienestar. El arte como medio para reflejar las dificultades de integración de niños autistas en el Centro de Terapia del Lenguaje (CTL) de la ciudad de Huaquillas. Los niños autistas enfrentan numerosos problemas para desenvolverse en entornos familiares, educativos, culturales y sociales. En el contexto familiar, pueden tener dificultades para comunicarse y formar vínculos emocionales con sus seres queridos. Además, en el ámbito educativo, suelen enfrentar barreras en el aprendizaje y la socialización, lo que puede llevar a la exclusión y el aislamiento de los niños con TEA. A menudo se malinterpreta a este segmento de la población, lo que dificulta su integración en actividades comunitarias. La falta de comprensión y aceptación por una parte de la sociedad puede conducir a la discriminación y el rechazo. Este estudio se interesa en los problemas de niños con TEA, el arte tiene el poder de comunicar y visibilizar estas experiencias de manera profunda y accesible. Asimismo, es considerado digno de ser estudiado desde las artes porque las obras pueden reflejar las realidades complejas que enfrentan estos niños, generando empatía y conciencia en la comunidad. La relación del arte con este objeto de estudio radica en su capacidad para cuestionar y desafiar percepciones sociales, promoviendo cambios positivos en la inclusión y el apoyo a los niños autistas. En consecuencia, el arte no solo documenta sus desafíos, sino que también ofrece una plataforma para expresar sus voces y experiencias; para transformar actitudes y fomentar una mayor comprensión y aceptación en la sociedad.
Keywords: AUTISMO; INCLUSION; EDUCACION; ARTE; TALLER